2017
DOI: 10.3389/fcimb.2017.00447
|View full text |Cite
|
Sign up to set email alerts
|

Alizarin and Chrysazin Inhibit Biofilm and Hyphal Formation by Candida albicans

Abstract: Candida albicans is one of the most common pathogen causes fungal infections. This opportunistic pathogen can form biofilms comprised of yeast, hyphae and pseudo hyphal elements, and the hyphal form C. albicans considered as probable virulence factor. We investigated the antibiofilm activities of 13 quinones and anthraquinones related compounds against C. albicans biofilms by using crystal violet and 2,3-bis (2-Methoxy-4-Nitro-5-Sulfo-phenyl)-2H-Tetrazolium-5-Carboxanilide (XTT) reduction assays to assess inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 62 publications
2
63
1
Order By: Relevance
“…Initially, we investigate whether indole derivatives affect biofilm formation by fluconazole‐resistant C. albicans DAY185 (Manoharan et al ., 2017a,b), and cell growth was simultaneously measured in the presence of indole derivatives. Of the 34 commercially available indole derivatives examined, 7‐benzyloxyindole, 4‐fluoroindole and 5‐iodoindole significantly reduced biofilm formation at concentrations of 0.1 and 0.5 mM (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we investigate whether indole derivatives affect biofilm formation by fluconazole‐resistant C. albicans DAY185 (Manoharan et al ., 2017a,b), and cell growth was simultaneously measured in the presence of indole derivatives. Of the 34 commercially available indole derivatives examined, 7‐benzyloxyindole, 4‐fluoroindole and 5‐iodoindole significantly reduced biofilm formation at concentrations of 0.1 and 0.5 mM (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, DAY185 is resistant to the commercial antifungal fluconazole (MIC ~ 512 μg ml −1 ) (Manoharan et al ., 2017a,b). A single colony was inoculated into 25 ml of PDB and incubated for overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts by Lee and co-workers have demonstrated that alizarin (10 mg mL À1 ) is an effective inhibitor of biofilm formation for three Staphylococcus aureus (S. aureus) strains and one Staphylococcus epidermidis strain. 20,21 Biofilms are complex bacterial communities that can facilitate antibiotic resistance and impair wound healing. 22 Hence, the development of new systems that can effectively treat or inhibit biofilm formation are highly desirable.…”
mentioning
confidence: 99%
“…[23][24][25] ARS was able to inhibit biofilm formation for S. aureus MRSA252 and S. aureus H560 at 100 mM when added during the lag phase of growth (0 h), similar to other reports in the literature for Alizarin. 21 However, ARS was unsuccessful in the inhibition of P. aeruginosa PAO1 and E. coli NCTC 10418 biofilms at concentrations below 100 mM (see Fig. S14-S16, ESI †).…”
mentioning
confidence: 99%